Nucleic acid recognition orchestrates the anti-viral response to retroviruses - Stavrou, Spyridon (Cell Host Microbe, 2015)
Intrinsic restriction factors and viral nucleic-acid sensors are important for the anti-viral response. Here, we show how upstream sensing of retroviral reverse transcripts integrates with the downstream effector APOBEC3, an IFN-induced cytidine deaminase that introduces lethal mutations during retroviral reverse transcription. Using a Murine Leukemia Virus (MLV) variant with an unstable capsid that induces a strong IFNβ antiviral response, we identify three sensors, IFI203, DDX41 and cGAS, required for MLV nucleic-acid recognition. These sensors then signal using the adaptor STING, leading to increased production of IFNβ and other targets downstream of the transcription factor IRF3. Using knockout and mutant mice, we show that APOBEC3 limits the levels of reverse transcripts that trigger cytosolic sensing, and that nucleic-acid sensing in vivo increases expression of IFN-regulated restriction factors like APOBEC3 that in turn reduce viral load. These studies underscore the importance of the multiple layers of protection afforded by host factors.